Characteristics of the initial dengue outbreaks in a region without dengue prior to mid-2009 in a dengue-endemic country - Kalamathy, M.; Coonghe, P.A.D.; Kumanan, T.; Murugananthan, A.; Gowri, S.; Sivansuthan, S.; Sathiadas, M.G.; Ketheesan, N.; Careem, F.A.; Noordeen, F. (JIDC, 2023)
Introduction: The present study evaluated the characteristics of the initial dengue outbreaks in the Jaffna peninsula, a region without dengue prior to mid-2009 in dengue-endemic Sri Lanka, a tropical island nation. Methodology: This is a cross-sectional study conducted using a total of 765 dengue patients’ clinical data and samples collected from the Teaching Hospital, Jaffna during the initial dengue outbreaks. Clinical, non-specific, and specific virological laboratory characteristics including the platelet count, NS1 antigen, and anti-DENV IgM/IgG were evaluated as correlates of dengue virus (DENV) infection in the two initial outbreaks of 2009/2010 and 2011/2012 in Northern Sri Lanka. Results: Firstly, affected age and clinical characteristics were significantly different between the outbreaks (p < 0.005). Secondly, NS1 antigen detection in patients with fever days < 5 was statistically significant (p < 0.005). Thirdly, platelet count, detection of NS1 antigen, and antiDENV IgM/IgG profiles were adequate to diagnose 90% of the patients; hepatomegaly and platelet count of < 25,000/mm3 were identified as predictors of severe disease. Fourthly, secondary DENV infections were detected in the early stages of the illness in many patients. Finally, infecting DENV serotypes were different between the two outbreaks. Conclusions: Clinical and non-specific laboratory characteristics and the infecting DENV serotypes between the two initial outbreaks in Northern Sri Lanka were significantly different. NS1 antigen, anti-DENV IgM/IgG, and platelet counts were identified 90% of the dengue patients. Hepatomegaly and platelet count of < 25,000/mm3 were able to predict the disease severity in this study.
Keywords: Dengue; Initial outbreaks; Clinical; Laboratory; Virological characteristics